(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The content of technological education is updated in accordance with the development of science and technology, the emergence of new technologies. But due to the inertia of the educational system, such an update is almost always too late. New technologies and their use in all spheres of human activity are rapidly changing modern production, world markets, economy and social sphere.